Frontiers in the Acquisition of Literacy - Claire M. Fletcher-Flinn (Frontiers Research Topics, 2015)
Learning to read, and to spell are two of the most important cultural skills that must be acquired by children, and for that matter, anyone learning a second language. We are not born with an innate ability to read. A reading system of mental representations that enables us to read must be formed in the brain. Learning to read in alphabetic orthographies is the acquisition of such a system, which links mental representations of visual symbols (letters) in print words, with pre-existing phonological (sound) and semantic (comprehension) cognitive systems for language. Although spelling draws on the same representational knowledge base and is usually correlated with reading, the acquisition processes involved are not quite the same. Spelling requires the sequential production of letters in words, and at beginning levels there may not be a full degree of integration of phonology with its representation by the orthography. Reading, on the other hand, requires only the recognition of a word for pronunciation. Hence, spelling is more difficult than reading, and learning to spell may necessitate more complete representations, or more conscious access to them. The learning processes that children use to acquire such cognitive systems in the brain, and whether these same processes are universal across different languages and orthographies are central theoretical questions. Most children learn to read and spell their language at the same time, thus the co-ordination of these two facets of literacy acquisition needs explication, as well as the effect of different teaching approaches on acquisition. Lack of progress in either reading and/or spelling is also a major issue of concern for parents and teachers necessitating a cross-disciplinary approach to the problem, encompassing major efforts from researchers in neuroscience, cognitive science, experimental psychology, and education. The purpose of this Research Topic is to summarize and review what has been accomplished so far, and to further explore these general issues. Contributions from different perspectives are welcomed and could include theoretical, computational, and empirical works that focus on the acquisition of literacy, including cross-orthographic research.